K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 10 2021

(X-\(\frac{2}{3}\))2-1=8

(X-\(\frac{2}{3}\))2   =8+1=9

(X-\(\frac{2}{3}\))2=(\(\pm\)3)2

Vậy x-\(\frac{2}{3}\)=3 hoặc x-\(\frac{2}{3}\)=-3

       x     =3+\(\frac{2}{3}\)    x       =-3+\(\frac{2}{3}\)

       x      =\(\frac{11}{3}\)    x        =\(\frac{-7}{3}\)

==>x\(\in\){\(\frac{11}{3}\);\(\frac{-7}{3}\)}

Hok tốt!

28 tháng 8 2019

1)1/9 x 3x = 2187:81=27

            3x=27:1/9=243=35

            =>x=5

  

28 tháng 8 2019

\(\frac{1}{9}.3^4.3^x=3^7\)

\(\Leftrightarrow3^x=3^7:\frac{1}{9}:3^4=243\)

\(\Leftrightarrow3^x=3^5\)

\(\Leftrightarrow x=5\)

a: Đặt f(x)=0

=>3/4x=1/8

=>x=1/8:3/4=1/8x4/3=4/24=1/6

b: Đặt H(x)=0

=>-5x+30=0

=>x=6

c: Đặt G(x)=0

=>(x-3)(x-4)=0

=>x=3 hoặc x=4

d: Đặt K(x)=0

=>(x-9)(x+9)=0

=>x=9 hoặc x=-9

e: Đặt M(x)=0

=>(x+8)(x-1)=0

=>x=-8 hoặc x=1

Bài 8:

a: \(\left(\dfrac{2}{5}+\dfrac{3}{4}\right)^2=\left(\dfrac{8+15}{20}\right)^2=\left(\dfrac{23}{20}\right)^2=\dfrac{529}{400}\)

b: \(\left(\dfrac{5}{4}-\dfrac{1}{6}\right)^2=\left(\dfrac{15}{12}-\dfrac{2}{12}\right)^2=\left(\dfrac{13}{12}\right)^2=\dfrac{169}{144}\)

18 tháng 3 2020

\(\left(x-\frac{1}{2}\right)^2=0\)

\(\Leftrightarrow\left(x-\frac{1}{2}\right)^2=0^2\)

\(\Leftrightarrow x-\frac{1}{2}=0\)

\(\Leftrightarrow x=\frac{1}{2}\)

Vậy x = 1/2

\(\left(x-2\right)^2=1\)

\(\Leftrightarrow\left(x-2\right)^2=1^2\)

\(\Leftrightarrow x-2=1\)

\(\Leftrightarrow\orbr{\begin{cases}x-2=1\\x-2=-1\end{cases}\Leftrightarrow\orbr{\begin{cases}x=3\\x=1\end{cases}}}\)

Vậy x = 3 hoặc x = 1

\(\left(2x-1\right)^3=-8\)

\(\Leftrightarrow\left(2x-1\right)^3=\left(-2\right)^3\)

\(\Leftrightarrow2x-1=-2\)

<=> 2x = -1

<=> x = -0,5

Vậy x = -0,5

18 tháng 3 2020

\(\left(x-\frac{1}{2}\right)^2=0\)

\(x-\frac{1}{2}=0\)

\(x=\frac{1}{2}\)

\(\left(x-2\right)^2=1\)

\(\Leftrightarrow\orbr{\begin{cases}x-2=1\\x-2=-1\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=1+2\\x=-1+2\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=3\\x=1\end{cases}}\)

Vậy\(x\in\left\{3;1\right\}\)
\(\left(2x-1\right)^3=-8\)

\(\left(2x-1\right)^3=\left(-2\right)^3\)

\(2x-1=-2\)

\(2x=\left(-2\right)+1\)

\(2x=-1\)

\(x=-1\times2\)

\(x=-2\)

\(x\left(\frac{1}{2}\right)^2=\frac{1}{16}\)

\(x\left(\frac{1}{2}\right)^2=\left(\frac{1}{4}\right)^2\)

\(\Leftrightarrow\orbr{\begin{cases}x\frac{1}{2}=\frac{1}{4}\\x\frac{1}{2}=-\frac{1}{4}\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{4}:\frac{1}{2}\\x=-\frac{1}{4}:\frac{1}{2}\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=\frac{1}{2}\\x=-\frac{1}{2}\end{cases}}}\)

12 tháng 11 2019

ai nhNH MK K

23 tháng 4 2020

cảm ơn bạn nha

7 tháng 9 2016

\(a,\frac{8^{12}.5^{21}}{2^{17}.10^{19}}=\frac{\left(2^3\right)^{12}.5^{21}}{2^{17}.2^{19}.5^{19}}=\frac{2^{36}.5^{21}}{2^{36}.5^{19}}=25\)

\(b,\left(x-5\right).\left(x+\frac{1}{2}\right)=0\)

\(\Rightarrow x-5=0\)hoặc  \(x+\frac{1}{2}=0\)

\(x=5\)hoặc \(x=-\frac{1}{2}\)

\(c,\left|x-6\right|-\frac{1}{2}=\frac{3}{2}\)

\(\left|x-6\right|=2\)

\(\Rightarrow x-6=2\)hoặc  \(x-6=-2\)

\(x=8\)hoặc  \(x=4\)